The cost-effectiveness of comprehensive school reform and rapid assessment. - Yeh, Stuart S. (Education Policy Analysis Archives, 2008)
Analysis of the cost-effectiveness of 29 Comprehensive School Reform (CSR) models suggests that all 29 models are less cost-effective than an alternative approach for raising student achievement, involving rapid assessment systems that test students 2 to 5 times per week in math and reading and provide rapid feedback of the results to students and teachers. Results suggest that reading and math achievement could increase approximately one order of magnitude greater for every dollar invested in rapid assessment rather than CSR. The results also suggest that reading and math achievement could increase two orders of magnitude for every dollar invested in rapid assessment rather than class size reduction and three orders of magnitude for every dollar invested in rapid assessment rather than high quality preschool.